FoMO And Discounts: Why Generation Z Can't Resist Online Shopping? - Eva Sofiana; Rina Suthia Hayu (Management Analysis Journal, 2025)
This study  aims to explore the influence of social media influencers, fear of missing out (FoMO), shopping lifestyle, and discount prices on impulse buying among Generation Z TikTok and Instagram users in Indonesia. The objective is to identify key factors influencing Gen Z’s online impulse buying, highlighting the urgency due to the rising trend of digital-driven impulsive consumption. Using a quantitative approach, this study analyzed data from 130 respondents selected through random sampling techniques. Data analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS) reveals that social media influencers, fear of missing out (FoMO), and discount prices positively influence impulse buying, with FoMO having the most significant influence. However, the shopping lifestyle was found to have no significant influence on impulse buying. These findings have important implications for marketers, suggesting that they optimize collaboration with influencers who match the target market, design promotional strategies that utilize FoMO elements ethically, and implement structured discount pricing strategies. For consumers, this study encourages awareness of the influence of influencers and FoMO on purchasing decisions, as well as the importance of self-control. For companies, it provides insights to develop effective digital marketing strategies by leveraging FoMO and discounts, especially to attract Gen Z.